Reproductive performance and organochlorine pollutants in an Antarctic marine top predator: The south polar skua - Bustnes, Jan O; Tveraa, Torkild; Varpe, Øystein; Henden, John A; Skaare, Janneche U (Environment International, 2007)
Keywords: Dronning Maud Land; forurensning; miljø; ornitologi; polarområdene; reproduksjon; økologi

Organochlorines in Antarctic and Arctic Avian Top Predators: A Comparison between the South Polar Skua and Two Species of Northern Hemisphere Gulls - Bustnes, Jan O; Tveraa, Torkild; Henden, John A; Varpe, Øystein; Janssen, Kirstin; Skaare, Janneche U (Environmental Science & Technology, 2006)
Different organochlorine compounds (OCs) were measured in the blood of breeding south polar skuas (Catharacta maccormicki) at Svarthamaren, Dronning Maud Land (Antarctica) and compared to those in two species of northern hemisphere gulls: the Arctic glaucous gull (Larus hyperboreus) and the subarctic great black-backed gull (Larus marinus). The skuas had 8% and 29% of the ∑OC levels (45 ng/g, wet weight) of glaucous gulls (591 ng/g) and great black-backed gulls (158 ng/g), respectively. Polychlorinated biphenyls (PCBs) and p,p‘-dichlorodiphenyldichloroethylene (p,p‘-DDE) were very low in skuas compared to northern gulls, but the mean hexachlorobenzene (HCB) level was 1.7 times higher than in great black-backed gulls and one-third of the glaucous gull level. Mirex levels in skuas were among the highest reported in birds, the mean level being 3 and 26 times higher than those in glaucous gull and great black-backed gulls, respectively. In skuas, the mean levels of HCB, oxychlordane, p,p‘-DDE, and PCBs increased by about 30% during a 2-week period, and mirex increased by nearly 60%. In glacuous gulls, HCB, p,p‘-DDE, and PCBs increased by 10−20%. For HCB, mirex, and oxychlordane, only a relatively small proportion of the increase in skuas could be explained by changes in lipid pools and the levels at first sampling, compared to glaucous gulls. Thus, skuas were probably accumulating these compounds when present in Antarctica. p,p‘-DDE and PCB levels, in contrast, seemed much more stable in the skuas. Relatively high levels of mirex and HCB in south polar skuas are concerning with regard to potential adverse effects.
Publisher: American Chemical Society
Keywords: Dronning Maud Land; kjemiske analyser; ornitologi; polarområdene; sjøfugler

Norge i Antarktis : fra erobring til moderne forskning - Winther, Jan-Gunnar; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Tveraa, Torkild; Monsen, Oddbjørn (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene